Comparing the principles of lexicography and lexicographic processes of the Khal and Moein Persian languages. - Akbari, Nasrin Ali; Akbari, Forough Ali (Sulaimani Journal for Humanities, 2023)
This research examines two monolingual dictionaries of Kurdish words, the Khal Dictionary, by Sheikh Mohammadi Khal (1904-1989), a Kurdish scholar, jurist, commentator, jurist, and lexicographer, born in Sulaymaniyah, Iraq, and the Persian Dictionary by Dr. Mohammad Moin (1911-1971), born in Rasht, the first Persian language graduate from Tehran University, professor, researcher, author, head of the Dehkhoda Dictionary after Ali Akbar Dehkhoda, and creator of the Moin Persian Dictionary, in terms of entry information in a comparative manner. Data will be collected through a library method and the research will be conducted using a descriptive-analytical method. The sample size will be 50 words randomly selected from all letters of the alphabet, with 25 words for each dictionary, and it seeks to answer these questions: What are the similarities and differences between the two cultures? How have these two cultures presented words that sound alike, have the same spelling, and have multiple meanings? Which one is closer to international lexicographic standards?
Keywords: Lexicography; monolingual dictionary; vocabulary entry; Khal dictionary; and Moeen Persian dictionary